2020
DOI: 10.1016/j.jse.2020.03.051
|View full text |Cite
|
Sign up to set email alerts
|

Suprascapular nerve decompression in addition to rotator cuff repair: a prospective, randomized observational trial

Abstract: Background: Tear and retraction of the supraspinatus (SS) and infraspinatus (IS) musculotendinous units and/or their repair may be associated with traction damage to the suprascapular nerve, potentially responsible for pain or weakness of the rotator cuff (RC). Arthroscopic release of the transverse scapular ligament at the suprascapular notch has been advocated to prevent or treat suprascapular nerve impairment associated with RC retraction and/or repair. The effect of this procedure on preoperative normal ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 44 publications
(51 reference statements)
0
27
0
Order By: Relevance
“…They concluded that the patients with nerve release presented with better functional recovery and less pain at the final follow-up. 21,22 However, Gerber et al, 23 in a prospective randomized trial of a small number of patients (N ¼ 19), did not find any difference between the release and non-release groups.…”
Section: Discussionmentioning
confidence: 93%
“…They concluded that the patients with nerve release presented with better functional recovery and less pain at the final follow-up. 21,22 However, Gerber et al, 23 in a prospective randomized trial of a small number of patients (N ¼ 19), did not find any difference between the release and non-release groups.…”
Section: Discussionmentioning
confidence: 93%
“…In the cases of rotator cuff tear and spinoglenoid notch cyst from a superior labrum tear, there is compelling evidence that suprascapular nerve decompression is unnecessary in most cases. 9,10 Moreover, transverse scapular ligament release before rotator cuff repair with confirmation of free mobility of the suprascapular nerve after release can result in subtle nerve injury detectable on electromyography, even in expert hands. 10 While we do not decompress the suprascapular nerve at the time of rotator cuff repair, we do decompress any large spinoglenoid notch cyst that is causing compressive neuropathy even if we perform a SLAP repair.…”
Section: University Of Maryland School Of Medicinementioning
confidence: 99%
“…9,10 Moreover, transverse scapular ligament release before rotator cuff repair with confirmation of free mobility of the suprascapular nerve after release can result in subtle nerve injury detectable on electromyography, even in expert hands. 10 While we do not decompress the suprascapular nerve at the time of rotator cuff repair, we do decompress any large spinoglenoid notch cyst that is causing compressive neuropathy even if we perform a SLAP repair. 11 We firmly believe that opening the lateral aspect of a large spinoglenoid notch cyst has negligible downside and ensures immediate relief of the compressive neuropathy, which is the indication for surgery in these patients.…”
Section: University Of Maryland School Of Medicinementioning
confidence: 99%
“…The efficacy of concomitant suprascapular nerve decompression at the time of rotator cuff repair remains controversial. Gerber et al 7 investigated shoulder function, magnetic resonance imaging (MRI), and electromyography (EMG) and nerve conduction studies in 19 patients undergoing rotator cuff repair randomized into 2 groups: 1 group with concomitant suprascapular nerve decompression and 1 group without such decompression. All patients had normal preoperative EMG and nerve conduction studies and mild fatty degeneration of the supraspinatus and infraspinatus muscles (Goutallier grade 1 or 2).…”
Section: Rotator Cuff Repairmentioning
confidence: 99%